A Correlation between Working Environment and Job Experience Toward Culture Shock among Indonesian Nurses in Japan - Erwin Yektiningsih; Asti Melani Astari; Yulian Wiji Utami (Jurnal Ners, 2021)
Introduction: Indonesian nurses living and working in Japan with a culture likely to be very different from their own may be additional sources of culture shock, feeling confusion and discomfort when living in a new country. They also experience difficulties in maladaptive adjustments to the new environment to overcome culture shock, then they get stressed in a working environment which can   decrease   work motivation and quality of performance.Methods: This study used a cross-sectional approach with a non-probability sampling method. The sample is 90   Indonesian nurses having been working in Japanese hospitals, both those passing the National Board Examination (NBE) and those not. Working environment (job satisfaction, colleague, rule of employment) and job experience were independent variables and culture shock was dependent variable. Work environment research instruments were from the revised questionnaire modification Scale of Socio-Cultural Adaptation (SCAS-R), the substance of work performance, job experience questionnaire and the Culture Shock Questionnaire (CSQ). Data analysis used Spearman-rho and multiple logistic regression statistical tests.Results: The average of respondents who did not experience culture shock or normal  was 44 (49%) and respondents who experienced culture shock were a poor level of 36 (40%) and moderate level of 10 (11%). Job satisfaction (ρ value = 0.001) and colleague (ρ value = 0.000) have a significant correlation with culture shock. Rule of employment (ρ value = 0.174) and job experience (ρ value = 0.209) were not significant with culture shock. Multiple logistic regression analysis was conducted to figure out the predictors that influence the change in culture shock status while a colleague (β = 2.445, p value < 0.000).Conclusion: The results of the research showed that colleagues in the work environment had a significant influence effect on cultural shock. Therefore, it is necessary to provide social support to adaptive adjustment and stress management to Indonesian nurses in Japan so that they can impact increased quality performance.